2013
DOI: 10.1159/000345598
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Nutritional Programming of Obesity: Mother-Child Cohort Studies

Abstract: Background: The obesity epidemic has resulted in more overweight/obese women before and during pregnancy. Their offspring tend to have higher birth weights and more body fat, and carry an increased risk of obesity later in life. These effects may partly be related to the heightened risk of gestational diabetes, occurring in at least 16% of all pregnancies irrespective of current body weight. Methods: An ILSI Europe workshop reviewed the key contributors leading to adverse outcomes in pregnancy and childhood, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 145 publications
1
74
0
10
Order By: Relevance
“…Both maternal weight and stature may influence the linear growth potential and weight gain of the children. These circumstances have been explained by the sharing of genetic, socioeconomic and environmental characteristics (Addo et al, 2013;Araújo et al, 2010;Felisbino-Mendes et al, 2014;Figueroa Pedraza et al, 2013;Sichieri et al, 2010;Symonds et al, 2013). Current analysis revealed a strong association between birth weight and the anthropometric nutritional status of children, with similar results in previous studies, such as studies based on municipal or state population data (Jesus, Castelão, Vieira, Gomes, & Vieira, 2014;Figueiroa et al, 2012;Rissin et al, 2011) and in populations marked by social inequity Lang et al, 2011;Silveira et al, 2010).…”
Section: Discussionsupporting
confidence: 84%
“…Both maternal weight and stature may influence the linear growth potential and weight gain of the children. These circumstances have been explained by the sharing of genetic, socioeconomic and environmental characteristics (Addo et al, 2013;Araújo et al, 2010;Felisbino-Mendes et al, 2014;Figueroa Pedraza et al, 2013;Sichieri et al, 2010;Symonds et al, 2013). Current analysis revealed a strong association between birth weight and the anthropometric nutritional status of children, with similar results in previous studies, such as studies based on municipal or state population data (Jesus, Castelão, Vieira, Gomes, & Vieira, 2014;Figueiroa et al, 2012;Rissin et al, 2011) and in populations marked by social inequity Lang et al, 2011;Silveira et al, 2010).…”
Section: Discussionsupporting
confidence: 84%
“…So the relationship between maternal gestational obesity and offspring obesity could be explained by the effect of the exposure to high maternal plasma glucose, free fatty acid and amino acids concentration during pregnancy carrying lifelong changes in fetal appetite, neuroendocrine function or energy metabolism and an increased risk for metabolic and cardiovascular diseases after birth 1,4 .…”
Section: Authormentioning
confidence: 99%
“…According to observational studies, carried out in high income countries, maternal lifestyle, dietary habits, physical activity and work hours could influence offspring size at birth, and weight development in childhood 1,2,3 . Pre-pregnancy and gestational maternal body composition may impact offspring body fat mass at birth, in childhood and in adolescence, and may also predict the risk of obesity in adulthood 4,5,6,7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…A third of American women of reproductive age are obese (Orsi et al, 2011). Now, epidemiological studies have shown increased birth weight in new-borns from obese mothers, associated with a higher risk of developing obesity in the future (Muhlhausler et al, 2013;Symonds et al, 2013). Epidemiological studies, experimentations on animals and placental models have shown the critical role played by the intrauterine environment in foetal development, including a direct transmission of obesity or metabolic pathologies (Dong et al, 2013;Symonds et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Now, epidemiological studies have shown increased birth weight in new-borns from obese mothers, associated with a higher risk of developing obesity in the future (Muhlhausler et al, 2013;Symonds et al, 2013). Epidemiological studies, experimentations on animals and placental models have shown the critical role played by the intrauterine environment in foetal development, including a direct transmission of obesity or metabolic pathologies (Dong et al, 2013;Symonds et al, 2013). For example, the male offspring of mice with gestational obesity developed excess weight, insulin resistance and hyperleptinemia at adulthood, without any post-natal obesogenic influence (Dahlhoff et al, 2014).…”
Section: Introductionmentioning
confidence: 99%